Interferences Of English-Japanese Language In The Covid-19 Pandemic - Irzam Sarif S; Dadang Suganda (IZUMI, 2020)
Interference is the use of other language elements by individual bilingual languages. Several researchers have researched interference, but no one has examined the interference with Covid-19 as an object. This study aims to describe the forms of English language phonological, morphological, and syntactic interference to the Japanese language. This study used a qualitative descriptive research method, with data sources in the form of vocabulary or terms during the Covid-19 pandemic. The results of this study indicated that the phonological interference forms found are phoneme addition, phoneme insertion, and phoneme substitution, which are caused by differences in syllables. The morphological and syntax interference in the form of compound words and phrases caused by differences in the class of terms that form between the two languages.